Future agricultural conditions in the Nepal Himalaya - A fuzzy logic approach using high resolution climate scenarios - Heider, Katharina; Weinzierl, Thomas; Schwab, Niels; Bobrowski, Maria; Schickhoff, Udo (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Until the end of the 21st century, ongoing climate change is expected to trigger major changes in site conditions and vertical species distributions in high mountain regions such as the Himalaya. Altitudinal ranges of species used as staple crops in Himalayan agriculture and currently suitable cultivation areas will be affected as well. Changing climatic variables such as temperature and precipitation will modify agricultural land-use options, and assessments of future crop growth conditions are in high demand. This GIS-based approach utilizes high resolution climate data of the present and two future scenarios and relates them to bioclimatic requirements of the five most important crops grown in Nepal: rice, maize, wheat, finger millet and potato. It takes into account soil pH as a basic constraint for the individual crop. The three factors  temperature, precipitation,and soil pH are then combined using a fuzzy logic algorithm. The assessment visualizes the expected shifts in suitable cultivation zones for the individual crops. The results show that wheat is likely to experience the most severe loss of crop suitability until the end of the 21st century, while the cultivation of rice is likely to benefit.